(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Giftednessis frequently not evenly distributed throughout all intellectual spheres; anindividual may excel in solving logic problems and yet be a poor speller;another gifted individual may be able to read and write at a far above averagelevel and yet have trouble with mathematics. It is possible there are differenttypes of giftedness with their own unique features, just as there are differenttypes of developmental delay. Giftedness may become noticeable in individuals atdifferent points of development. While early development (i.e. speaking orreading at a very young age) usually comes with giftedness, it is not adeterminant of giftedness. The preschool years are when most gifted childrenbegin to show the distinctive characteristics mentioned above. As the child becomesolder, classes that are ’too easy’ and emotional issues may slow or obstructthe rate of intellectual development.